State Preemption of Municipal Laws and Policies that Protect Immigrant Communities: Impact on Latine Health and Well-Being in North Carolina. (8th March 2022) - Mann-Jackson, Lilli; Simán, Florence M.; Hall, Mark A.; Alonzo, Jorge; Linton, Julie M.; Rhodes, Scott D.
Background: Some U.S. municipalities have proclaimed themselves "sanctuary cities" and/or adopted laws and policies limiting local involvement in enforcement of federal immigration policies. Several states, however, have adopted laws that preempt municipal laws and policies designed to protect immigrants. We explored the consequences of House Bill (H.B.) 318, one such preemption law in North Carolina (NC), on the health and well-being of Latine immigrants. Methods: We conducted focus groups with Latine immigrants (n=49) and in-depth interviews with representatives from health, social service, and immigrant-serving organizations and local government (including law enforcement) (n=21) in NC municipalities that, before HB 318, adopted laws and policies supporting immigrants. Data were analyzed using constant comparison. Results: Twelve themes emerged, including the positive impacts of municipal sanctuary laws and policies are limited by preemption and other state and federal actions; laws and policies like HB 318 are confusing, have a chilling effect on health services use, and make life harder overall for Latine communities; intensified federal immigration enforcement has increased fear among Latine communities; Trump administration policies worsened anti-immigrant climates; and use of community identification cards and greater information dissemination and inter-organization coordination can lessen the consequences of preemption and other restrictive laws and policies. Conclusion: State preemption of protective municipal laws and policies negatively and profoundly affects immigrant health and well-being. However, creative strategies have been implemented to respond to preemption. These findings provide critical data for decision-makers and community leaders regarding the detrimental impacts of preemption laws and mitigation of these impacts.